2015
DOI: 10.1016/j.ydbio.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Gdf5 progenitors give rise to fibrocartilage cells that mineralize via hedgehog signaling to form the zonal enthesis

Abstract: The sequence of events that leads to the formation of a functionally graded enthesis is not clearly defined. The current study demonstrates that clonal expansion of Gdf5 progenitors contributes to linear growth of the enthesis. Prior to mineralization, Col1+ cells in the enthesis appose Col2+ cells of the underlying primary cartilage. At the onset of enthesis mineralization, cells at the base of the enthesis express alkaline phosphatase, Indian hedgehog, and ColX as they mineralize. The mineralization front th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(155 citation statements)
references
References 43 publications
(83 reference statements)
8
146
0
1
Order By: Relevance
“…Recent studies showed that enthesis fibrocartilage cells are specified during embryonic stages, beginning at E14.5–15.5. The fibrocartilage transitional zone of the enthesis emerges from a specialized subpopulation of cells (likely derived from the Scx/Sox9 pool) that can be detected based on their hedgehog signaling activity (Gli1+) (Dyment et al, 2015; Schwartz et al, 2015). Gli1+ cells specified during embryonic stages ultimately give rise to the entire mature enthesis.…”
Section: Enthesesmentioning
confidence: 99%
“…Recent studies showed that enthesis fibrocartilage cells are specified during embryonic stages, beginning at E14.5–15.5. The fibrocartilage transitional zone of the enthesis emerges from a specialized subpopulation of cells (likely derived from the Scx/Sox9 pool) that can be detected based on their hedgehog signaling activity (Gli1+) (Dyment et al, 2015; Schwartz et al, 2015). Gli1+ cells specified during embryonic stages ultimately give rise to the entire mature enthesis.…”
Section: Enthesesmentioning
confidence: 99%
“…This step is critical to fix the soluble cytoplasmic GFP of transgenic animals within the limits of the cell. We have utilized the cryotape for a wide range of tissue types [5][6][7][8][9][10][11][12][13] . Laboratory personnel with limited histological experience can produce high-quality sections with this method.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have published a new high-throughput cryohistological method for assessing several response measures within a given section from mineralized tissue [5][6][7][8][9][10][11][12][13][14] . The process involves stabilizing the cryosection with frozen cryotape, adhering the taped section rigidly to a microscope slide, and conducting several rounds of staining and imaging on each section.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of mineral and orientation of the collagen fibers in the enthesis has been shown to influence its mechanical properties [19,24,25,26,27]. Recent studies have indicated that the Indian Hedgehog signaling pathway is involved in enthesis development and mineralization of the CFC, in part because its ablation results in decreased mineralization and less collagen imbedded in the mineralized tissues [28,29,30,31]. Similarly, alkaline phosphatase, whose expression is correlated to mineral formation, is expressed by the differentiated fibrocartilaginous cells [29].…”
Section: Discussionmentioning
confidence: 99%